Bio-derived carbon nanostructures for high-performance lithium-ion batteries. (April 2019) - Bakierska, Monika; Lis, Marcelina; Pacek, Joanna; Świętosławski, Michał; Gajewska, Marta; Tąta, Agnieszka; Proniewicz, Edyta; Molenda, Marcin
Abstract: Hierarchically arranged, nanostructured carbon aerogels (CAGs) derived from different types of starch were prepared through the gelatinization process, exchange of solvent and pyrolysis of organic precursors in an inert gas atmosphere. The morphology and structure of the obtained CAGs materials were characterized by scanning and transmission electron microscope (SEM, TEM) as well as Raman spectroscopy (RS). The electrochemical behavior of lithium cells based on the fabricated carbon electrodes was carried out using the most common techniques in electrochemical study, namely the galvanostatic charge/discharge tests (GCDT), electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The results showed that the obtained carbonaceous samples exhibit high reversible specific capacity of around 150–200 mAh/g under high C-rate (5C), depending on the origin of starch. Very good cycling stability, excellent coulombic efficiency and relatively high-rate capability of CAGs electrodes in lithium-ion batteries were attributed to their specific structure which ensures the fast transport kinetics of Li + ions and electrons. Graphical abstract: Image 10735074